The Father Intervention in Islamic Psychology Perspective on the Phenomenon of Fatherlessness in Indonesia: Father Intervention, Islamic Psychology. Fatherless, Indonesia, - Amrullah, Alfian (ROSYADA: Islamic Guidance and Counseling, 2025)
Indonesia ranks third in the world in the category of fatherless counties, according to data collected by UNICEF in 2021. This is a very concerning statistic in the case of Indonesia. The purpose of this study is to analyze the importance of the father's role in child intervention within the family. From an Islamic psychological perspective, according to Ibn Khaldun, in addressing this phenomenon, the researcher employed a qualitative literature review method with critical analysis, utilizing valid data and sources from various journals, theses, and dissertations. Previous research has found that a lack of intensity in the interaction between a father and a child can create awkwardness between the two. This can lead to dissatisfaction in communication and even other negative impacts. Furthermore, among the existing literature, there has been no research that explains the role of fathers in the family from an Islamic psychological perspective. Therefore, this research is considered very important and interesting to discuss in order to address some cases of fatherlessness in Indonesia. The conclusion of this study is that the role of the father in Islamic psychology is very important and irreplaceable within the family structure, with significant impacts on the formation of a child's character, soul, and intellectual development in the future.